Análise comparativa de sete normas técnicas de fornecimento de energia elétrica em tensão secundária para unidades individuais na região Sudeste - Camargo, Gabriela Maia [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
To ensure the proper fulfillment of electrical projects for residential installations is mandatory to follow the NBR 5410 and the technical standards for individual installations in secondary grid belonging to the electric utilities, because of contractual obligations. Every electric utility possess its own project method, described in standards of free access, which causes distinction in the dimensioning of residential electrical installations. It's intuitional to grant some asymmetries in the standards of electric utilities that possess concession area in different geographic regions, due to climatic influence in choosing power and use of some electrical devices, but not between standards of electric utilities in the same region, or even the same state. This study produces an economic analysis of the variance in method, power factor, power assumed to special loads and demand factor of seven electric utilities operating in different areas of Brazilian southeast region, by executing the dimensioning of the electric input branch of a residential installation following the seven different technical standards belonging to this electric utilities. Aiming to highlight the impact of electrical residential installations methods in the distribution grid, is also developed a hypothesis about transformers loading in residential areas, emphasizing the influence of calculated demands of installations in the loading of transformers and, thereafter, in technical losses of the distribution grid

Durante a realização de um projeto de instalações elétricas residenciais, é mandatória a observação da NBR 5410 e das normas técnicas de instalações individuais em rede secundária das concessionárias de distribuição de energia elétrica, por obrigações contratuais. Cada concessionária de energia possui sua própria metodologia descrita em documentos de livre acesso, o que leva a diferenças no resultado final do dimensionamento das instalações elétricas residenciais. É intuitivo admitir assimetrias nos métodos das concessionárias que possuam área de operação em diferentes regiões geográficas, devido à influência climática na potência e utilização de determinados aparelhos típicos em residências, porém não quando se refere às concessionárias pertencentes a uma mesma região ou mesmo estado. Este trabalho realiza uma análise econômica das divergências advindas dos métodos, fatores de potência e de demanda e das potências assumidas de cargas especiais de sete concessionárias com áreas concessão distintas nos quatro estados da região Sudeste. Para isto, realiza-se o dimensionamento do padrão de entrada para um estudo de caso de acordo com as normas técnicas das sete concessionárias. Visando ressaltar o impacto do método de cálculo das instalações residenciais na rede de distribuição, também é desenvolvida uma hipótese sobre o carregamento de transformadores em áreas exclusivamente residenciais com instalações semelhantes à do estudo de caso, evidenciando a influência da demanda calculada no carregamento dos transformadores e, consequentemente, nas perdas técnicas das redes de distribuição.
Comparative analysis of seven technical standards for electric power supply in secondary voltage for individual units in the Southeast region
Keywords: Normas técnicas (Engenharia); Instalações elétricas domiciliares; Energia elétrica - Distribuição; Transformadores eletricos; Standards, Engineering